Examining the urban morphology and defensive mechanisms of Dutch Malacca via topology, space syntax, and sDNA under the framework of CPTED theory - Weicong Li; Sharifah Salwa Syed Mahdzar; Khairul Anwar Mohamed Khaidzir (Humanities & Social Sciences Communications)
Abstract The fragmentation in Malacca’s urban space largely stems from historical planning issues, initially driven more by external pressures than developmental guidance. Based on Crime Prevention Through Environmental Design (CPTED) theory, space syntax, topological modeling and Spatial Design Network Analysis (sDNA) methods, this study compares the spatial characteristics of Malacca during the Dutch period and the early years of Malaysian independence and analyzes the process by which the urban fabric was shaped and its relationship to the geopolitical context. The early compact and matrix street network of Malacca was designed to protect against risk. The change in economic and political focus was reflected in a linear shift in urban centrality from inland to port. The transition in spatial depth from “constrained” to “free” reflected a shift in urban structure from “intensive” to “diffuse”. The results of the analysis of the sDNA and topological models in terms of urban centrality converge and reveal that Malacca already had a tendency towards polycentric development in 1958 and that the old network centers of 1764 still play a partial role. The study is consistent with the hypothesis that the main drivers of urban development in early Malacca were external pressures and were influenced by its colonial political and economic reconstruction. This study attempts to explain how spatial configurations responded to external risks, but the correspondence between certain historical events and the urban fabric remains unclear due to the scarcity of historical data.